1989
DOI: 10.1128/aem.55.6.1642-1644.1989
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Lignin-Related Compounds by Actinomycetes

Abstract: Evidence for activity against the lignin fraction of straw was produced for a range of actinomycete strains. Decolorization of the polymeric dye Poly R and oxidation of veratryl alcohol, indicators of ligninolytic activity in white rot fungi, and utilization of fractionated Kraft lignin and low-molecular-weight methoxylated aromatic compounds were the criteria used. The relationships between these activities and the solubilization of native lignin are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 16 publications
(20 reference statements)
1
25
0
Order By: Relevance
“…These three actinomycetes are the most widely studied lignocellulose-solubilising actinomycetes (MCCARTHY 1987). All 3 strains have been show to be able to utilise KRAFT lignin (BALL et al 1989, GIROUX et al 1988. The decolorisation of Poly R by culture filtrate confirmed that decolorisation was not due merely to biomass uptake suggesting that the dye was being actively degraded.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These three actinomycetes are the most widely studied lignocellulose-solubilising actinomycetes (MCCARTHY 1987). All 3 strains have been show to be able to utilise KRAFT lignin (BALL et al 1989, GIROUX et al 1988. The decolorisation of Poly R by culture filtrate confirmed that decolorisation was not due merely to biomass uptake suggesting that the dye was being actively degraded.…”
Section: Discussionmentioning
confidence: 96%
“…Strains and growth conditions : Actinomycete strains were maintained a spore suspensions and hyphal fragments in 20% (v/v) glycerol at -70 "C. Strains were routinely cultured on L-agar plates (HOPWOOD et al 1985), and distilled water suspensions of sporulating growth were used to inoculate shake flasks containing basal salts medium supplemented with Poly R (0.02% w/v; SIGMA Chemical Co.) ( Fig. 1 (BALL et al 1989). In cultures of S. viridosporus examining the inducibility of extracellular decolorising activity, Poly R was replaced by 1 % (w/v) of the appropriate substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The culture of each test organism (5.0 mL) from the sets of flasks was harvested every 3 days for determination of biomass. Growth of strains EOB and ROB was monitored by the dry weight method [24] because of their mycelial growth and pellets. Culture was filtered through a pre-weighted Whatman filter paper No 42; it was dried in an oven at 60°C, cooled in a desiccator and weight was recorded.…”
Section: Cultivation Of Isolates On Hydrocarbon and Biodegradation Stmentioning
confidence: 99%
“…There are many genera of actinomycetes and eubacteria which can degrade extracted lignin and DHP (Buswell and Odier, 1987). Many bacterial strains, especially actinomycetes, can solubilize and modify the lignin structure extensively, but their ability to miner-alize lignin is limited (Buswell and Odier, 1987;Ball et al, 1989;Eriksson et al, 1990;Godden et al, 1992). Actinomycetes degrade lignin as their primary metabolic activity and at high nitrogen levels compared to white-rot fungi, most of which degrade lignin via their secondary metabolism.…”
Section: Lignin-degrading Bacteriamentioning
confidence: 99%